Improved interoceptive awareness in chronic low back pain: a comparison of Back school versus Feldenkrais method. Issue 10 (8th May 2017) - Paolucci, Teresa; Zangrando, Federico; Iosa, Marco; De Angelis, Simona; Marzoli, Caterina; Piccinini, Giulia; Saraceni, Vincenzo Maria
Abstract: Purpose: To determine the efficacy of the Feldenkrais method for relieving pain in patients with chronic low back pain (CLBP) and the improvement of interoceptive awareness. Method: This study was designed as a single-blind randomized controlled trial. Fifty-three patients with a diagnosis of CLBP for at least 3 months were randomly allocated to the Feldenkrais (mean age 61.21 ± 11.53 years) or Back School group (mean age 60.70 ± 11.72 years). Pain was assessed using the visual analog scale (VAS) and McGill Pain Questionnaire (MPQ), disability was evaluated with the Waddel Disability Index, quality of life was measured with the Short Form-36 Health Survey (SF-36), and mind–body interactions were studied using the Multidimensional Assessment of Interoceptive Awareness Questionnaire (MAIA). Data were collected at baseline, at the end of treatment, and at the 3-month follow-up. Results: The two groups were matched at baseline for all the computed parameters. At the end of treatment (Tend), there were no significant differences between groups regarding chronic pain reduction ( p = 0.290); VAS and MAIA-N sub scores correlated at Tend ( R = 0.296, p = 0.037). By the Friedman analysis, both groups experienced significant changes in pain ( p < 0.001) and disability ( p < 0.001) along the investigated period. Conclusions: The Feldenkrais method has comparable efficacy as Back School in CLBP. Implications for rehabilitation: The Feldenkrais method is a mind–body therapy that is based on awareness through movement lessons, which are verbally guided explorations of movement that are conducted by a physiotherapist who is experienced and trained in this method. It aims to increase self-awareness, expand a person's repertoire of movements, and to promote increased functioning in contexts in which the entire body cooperates in the execution of movements. Interoceptive awareness, which improves with rehabilitation, has a complex function in the perception of chronic pain and should be investigated further in future research. The efficacy of the Feldenkrais method is comparable with that of BS for nonspecific chronic low back pain. The physician can recommend a body–mind rehabilitation approach, such as the Feldenkrais method, or an educational and rehabilitation program, such as BS, to the patient, based on his individual needs. The 2 rehabilitation approaches are equally as effective in improving interoceptive awareness.